Ang mga banal na krus ng Mayo [videorecording] - Medina, Susan Calo; Quintos, Floy (Travel Time, 1995)
A journey to the provinces to discover the traditions that celebrates the cross, the subli of Bauan, Batangas, Arraqui of Penaranda, Nueva Ecija, the Tapusan of Alitagtag, Batangas. Discovers dances and rituals that are performed prayers.